ON THE ALLEGED ERROR OF FORMAL OBJECTIONS TO NORMATIVE ERROR THEORY - JEREMIAH JOVEN JOAQUIN (Manuscrito, 2023)
Abstract According to Streumer and Wodak, a particular type of formal objection to normative error theory fails because it rests on a questionable assumption about the logical duality of the normative concepts of permissibility and impermissibility. In this discussion, we argue that there is an error in their indictment; as such, the formal objection to normative error theory might still prevail.